Programming PERL in the .NET Environment - Menaker, Yevgeny; Saltzman, Michael; Oberg, Robert (Addison-Wesley Professional, 2002)
Master PerlNET: the best of Perl and .NET together! Build fully compliant .NET components in Perl Practical, hands-on coverage of programming with Perl for Windows Forms, ADO.NET, ASP.NET, and more Running case study: see how Perl and .NET concepts work together in a business application Foreword by Dick Hardt, CEO of ActiveState Get the best of both worlds: Perl flexibility and .NET power! ActiveState's new PerlNET combines the incredibly flexible and useful Perl programming language with the immense resources and power of Microsoft's .NET platform. Programming Perl in the .NET Environment will help you make the most of Perl and .NET together-whether you're already familiar with Perl, or .NET, or neither. Using extensive code examples and a running case study, this book gives you practical insight for building robust object-oriented PerlNET applications, graphical user interfaces, database applications, and a whole lot more. A practical overview of the .NET Framework and Common Language Runtime Complete Perl programming review: operators, arrays, hashes, object-oriented Perl, and more Using and creating .NET components with PerlNET Leveraging the full power of the .NET Framework Classes Graphical Perl programming with Windows Forms Database integration with ADO.NET Easy Web application and service development with Perl for ASP.NET (PerlASPX) A detailed appendix on Visual Perl, the full-featured Perl plug-in for Visual Studio .NET.